THE ROLE OF COMPANY PERFORMANCE IN MEDIATING THE INFLUENCE BETWEEN ENTERPRISE RISK MANAGEMENT AND AUDIT COMMITTEE ON COMPANY VALUE - Sinta Vayendora; Desrir Miftah (Faculty of Economic and Social Science, Universitas Islam Negeri Sultan Syarif Kasim, 2024)
The aim of the research is to examine the influence between company risk management and audit committees on company value, with company performance as a mediating variable (Empirical Study on Infrastructure Subsector Group Companies Listed on the Indonesia Stock Exchange 2018–2022). The research population consisted of 65 companies, with a sample of 15 companies. The data testing method used is path analysis. The results of this research show that corporate risk management, audit committees, and company performance have a significant effect on company value, but corporate risk management, audit committees do not have a significant effect on company value. Company risk management also has a negative effect on company value and the audit committee has a negative effect on company performance. company performance has a positive effect on company value. Company performance is able to mediate Enterprise Risk Management on company value, but company performance is not able to mediate the audit committee on company value.